ECONOMIC IMPACT OF STIMULANTS APPLICATION ON RUBBER FARMING IN TANJUNG MAKMUR VILLAGE, OGAN KOMERING ILIR DISTRICT - Desi Aryani; Thirtawati Thirtawati; Hendi Febryansah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Rubber is one of Indonesia's leading plantation commodities. The main problem in natural rubber development is the low productivity level of rubber land. Based on the total area, Indonesia has a larger area than Thailand, but the rubber productivity in Indonesia is lower. One of the ways to increase rubber farming production is through a stimulant exploitation system. This study aims to compare income and the revenue ratio of rubber farmers who use stimulants and non-stimulants in Tanjung Makmur Village, Pedamaran Timur Sub-District. Sampling was done using the proportionate stratified random sampling method. The total sample for the analysis tool was 50 farmers. The data were processed using descriptive statistics and mathematics analysis. Based on the results, it is known that the production yield and income of rubber farmers who use stimulants are higher than those of non-stimulants. The difference in production is 15.08 kg/ha/month, and the difference in income is Rp. 20,973.22 per hectare per month. A small difference in income is due to the higher production costs of stimulant rubber farmers, while the price received is lower than that of non-stimulants. Based on the calculation of the R/C ratio, it is known that the R/C ratio of non-stimulants farmers is higher than that of stimulant farmers.